Study of Numerical Solution of Linear System of Equations by Using SOR Algorithm with \(0 - Ahmad, Najmuddin; Shaheen, Fauzia (Communications in Mathematics and Applications, 2021)
In this paper, we are studying new approaches in numerical accuracy of the linear system of equations by successive over-relaxation method, analyzing the convergence criteria of iterative methods and comparing the SOR method with other iterative methods. We have shown SOR method converges more rapidly with the others with the help of some typical examples. All the calculations have been performed with the help of MATLAB 2020R.
Keywords: Jacobi method; Gauss-Seidal method; Richardson method; SOR method; Spectral radius